PEDAGOGICAL EXPERIENCES OF TEACHING LEARNING, DURING COVID-19, AT NATIONAL UNIVERSITY OF CENTRAL PERU - Aquino Palacios, Ingrid Maritza (2023)
The research was born from the concern to understand the pedagogical experiences that the students of the Education Faculty of the National University of Central Peru have had, during teaching-learning, online education, in the context of COVID-19 in 2021-I academic semester. The type of research was descriptive, with a simple descriptive design of two groups. The sample was non-probabilistic, and was made up of students from the professional careers of Sciences Mathematics and Informatics; and Languages, Literature and Communication. The results obtained were that the students' pedagogical experiences were positive to the extent that they managed to develop the expected capabilities, the teaching methodology used by the teachers through the Microsoft Teams platform was also positive